2023
DOI: 10.3389/fvets.2023.1032429
|View full text |Cite
|
Sign up to set email alerts
|

Macromineral requirements for maintenance and growth in male and female hair sheep

Abstract: A better understanding of the nutritional requirements of sheep, especially in terms of minerals, is crucial for improving production. We estimated the net requirements for Ca, P, K, Mg, and Na for gain (NCag, NPg, NKg, NMgg, and NNag) and maintenance (NCam, NPm, NKm, NMgm, and NNam) in male and female hair sheep. Six datasets with 248 individual records of hair sheep (139 non-castrated males, 75 castrated males and 34 females) were used to estimate the net macromineral requirements for gain. To estimate the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Based on the total endogenous loss of Ca, the ARC (1980) estimated that the daily net Ca requirement for the maintenance of sheep is 0.016 g/kg of BW [ 8 ]. Recent research carried out by Herbster et al [ 11 ] suggests that the daily net Ca requirement for the maintenance of wool sheep is 0.024 g/kg of BW, which is 50% greater than that of the ARC (1980) value but slightly lower than the results in our study. In this study, the net Ca requirement for maintenance is similar to that reported by Pereira et al for Somali lambs [ 10 ], and it is lower than that reported by Sousa et al for Santa Ines sheep, which is 0.036 g/kg of BW [ 27 ].…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Based on the total endogenous loss of Ca, the ARC (1980) estimated that the daily net Ca requirement for the maintenance of sheep is 0.016 g/kg of BW [ 8 ]. Recent research carried out by Herbster et al [ 11 ] suggests that the daily net Ca requirement for the maintenance of wool sheep is 0.024 g/kg of BW, which is 50% greater than that of the ARC (1980) value but slightly lower than the results in our study. In this study, the net Ca requirement for maintenance is similar to that reported by Pereira et al for Somali lambs [ 10 ], and it is lower than that reported by Sousa et al for Santa Ines sheep, which is 0.036 g/kg of BW [ 27 ].…”
Section: Discussioncontrasting
confidence: 86%
“…The daily total Ca requirement was estimated to be 0.676 g/kg of BW 0.75 based on the group with the highest ADG (278.43 g/d), which resulted in the total Ca requirement of 10.75~12.71 g/d for 40-50 kg YSW rams. The NRC (2007) recommends a Ca requirement of 4.80–4.90 g/d for 8-month-old growing rams of 40–50 kg with a daily gain of 250 g [ 9 ], and Herbster et al [ 11 ] suggested a total Ca requirement of 4.70~5.16 g/d for 30 kg sheep gaining 200 g/d. The total Ca requirement value calculated in this study is almost twice the values calculated by the NRC (2007) and Herbster et al In addition, Ma et al reported that the Ca requirement of 35~50 kg Dorset × thin-tailed Han rams is 10.70–11.60 g/d [ 14 ], which is close to our results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation